A perspective on potential psychological risks and solutions of using virtual reality in palliative care - Woo, Olive K. L.; Lee, Antoinette M. (Frontiers in Virtual Reality, 2023)
Initial evidence suggests that virtual reality (VR) can effectively reduce palliative symptoms. While such findings shed positive light on the ability of VR exposure to improve patients' physical and emotional symptoms, VR could have downsides with adverse effects. As most of the reported adverse effects are related to physical risks or technical challenges, there is a scarcity of reports on possible psychological risks posed by VR exposure in palliative care settings, an area with considerable concerns. This is an area that is likely to have a significant impact on the future of clinical practice and research on the use of VR in palliative care. Based on the clinical experience of a registered clinical psychologist who has delivered VR in a palliative care unit for three years, we put forward a perspective on the potential psychological complications of using VR in palliative care. Our clinical experiences show that exposure to a desirable virtual environment that is beneficial to patients might not always align with realistic expectations, and that should the use of VR be considered, special precautions are needed to minimize possible psychological harms. This perspective article further proposes three approaches aiming to minimize possible psychological hazards: incorporation of psychological assessment before VR administration, psychological interventions right after VR, and professional training of the VR facilitators. We hope that our personally witnessed concerns and perspectives can alert future VR facilitators to the potential psychological hazards of using VR for patients receiving palliative care and inspire future research to minimize psychological harms.